Gilbert durand on the web of complexity: a possible meeting with edgar morin - Porto, Maria do Rosario Silveira (Revista Hipótese, 2021)
This article aims to show how two authors - Gilbert Durand and Edgar Morin -, each from their theoretical construction on the current reality, find themselves in the following common points: where do they start from, what is the conception of man they have and what they propose. Gilbert Durand develops his ideas based on an anthropology of the imaginary and Edgar Morin, on the notion of complexity and complex thinking. The article is concerned with establishing a parallel between the two, and never a comparison.
Keywords: Imaginary; Complexity; Paradigm; Semantic basin; Symbol